HUBUNGAN PERAN KADER POSYANDU DALAM MENINGKATKAN KESEHATAN DENGAN STATUS GIZI BALITA DI DESA TEGALTIRTO BERBAH SLEMAN - Siti Uswatun Chasanah (STIKES Wira Husada Yogyakarta, 2017)
Background: The role is very important cadre that includes the role of cadres as a motivator, administrator and educator. Cadres responsible for the implementation of the program posyandu. If the cadres are not active then posyandu also will be smooth and consequently the nutritional status of an infant or toddler can not be detected early with a clear. cadres played a role important in the development of the child and maternal health, because through women cadres getting health information first.Purpose of research: Knowing the role relationships Posyandu cadres in improving the health of children with the nutritional status of children in the Village TegaltirtoBerbahSleman. Method :This research is a quantitative research design cross sectional. The sampling technique using total sampling technique.The bivariate analysis using analysis Chi Square.Result : The result of using the Chi Square correlation test showed that there is a relationship between cadres role to the nutritional status of children (p-value 0,002 < 0,05) with Contingency Coefficient value of 0,523 which means that power conection being. Conclusion: There is a significant relationship between cadres role of the nutritional status of children in the Village Tegaltirto Berbah Sleman